Efektywność gospodarowania i inwestycje zagraniczne w okresie transformacji - Kurowski, Lech (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
As the outcome of the transition process in the formerly centrally planned economies, only viable ACS have been left on the market. Opening of the economy and the inflow of FDI have improved their performance through diffusion of new technologies and the spill-over effects of foreign investments. However, due to new imbalances brought about by the transition process itself, the long win macro economic efficiency has deteriorated. Considered to be one of the major engines of growth of the country, foreign investment already implemented in Poland did not always bring positive effects for the country. To prevent loss of the macro economic efficiency some institutional controls of market operation would be required. It is necessary as the market alone does not guarantee that the decisions at the micro level contribute to improvement of the macro economic situation looted at from a longer perspective. Only a systematic cost benefit analysis of larger FDI projects, made prior to the issue of investment permits could improve operational efficiency of a transition economy. The analysis should consider the net present economic value accruing to the nationals of the country and should cover the whole life time of the proposed project. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 232-247